2011
DOI: 10.1186/1556-276x-6-575
|View full text |Cite
|
Sign up to set email alerts
|

p-Cu2O-shell/n-TiO2-nanowire-core heterostucture photodiodes

Abstract: This study reports the deposition of cuprous oxide [Cu2O] onto titanium dioxide [TiO2] nanowires [NWs] prepared on TiO2/glass templates. The average length and average diameter of these thermally oxidized and evaporated TiO2 NWs are 0.1 to 0.4 μm and 30 to 100 nm, respectively. The deposited Cu2O fills gaps between the TiO2 NWs with good step coverage to form nanoshells surrounding the TiO2 cores. The p-Cu2O/n-TiO2 NW heterostructure exhibits a rectifying behavior with a sharp turn-on at approximately 0.9 V. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 27 publications
0
22
0
1
Order By: Relevance
“…[9] Cuprous oxide (Cu 2 O) has been applied as an attractive photoelectrode material for Page 4 of 30 A c c e p t e d M a n u s c r i p t 4 hydrogen production, because Cu 2 O is a p-type semiconductor with narrow bandgap (1.9-2.2 eV) of which the conduction band and valence band are close to the reduction and oxidation potential for water splitting. [10][11][12][13] As previous reports, [14,15] wide bandgap semiconductor (such as TiO 2 and ZnO) modified with Cu 2 O nanoparticles can significantly expand their absorption spectra range. However, the low interfacial area between different semiconductors directly influenced the separation efficiency of electrons and holes, so interfacial optimization of heterogeneous becomes a feasible way to further improving photoelectrochemical conversion efficiency.…”
Section: Introductionmentioning
confidence: 84%
“…[9] Cuprous oxide (Cu 2 O) has been applied as an attractive photoelectrode material for Page 4 of 30 A c c e p t e d M a n u s c r i p t 4 hydrogen production, because Cu 2 O is a p-type semiconductor with narrow bandgap (1.9-2.2 eV) of which the conduction band and valence band are close to the reduction and oxidation potential for water splitting. [10][11][12][13] As previous reports, [14,15] wide bandgap semiconductor (such as TiO 2 and ZnO) modified with Cu 2 O nanoparticles can significantly expand their absorption spectra range. However, the low interfacial area between different semiconductors directly influenced the separation efficiency of electrons and holes, so interfacial optimization of heterogeneous becomes a feasible way to further improving photoelectrochemical conversion efficiency.…”
Section: Introductionmentioning
confidence: 84%
“…Owing to its excellent properties, Cu 2 O has been used for many applications, such as photodiodes, [14][15][16] gas sensors, [17] resistive random access memory, [18,19] and thin film transistors. [13,15] The material can be prepared by a range of methods, such as sputtering, [13][14][15] chemical vapor deposition (CVD), [20,21] pulsed laser deposition A highly efficient n-Si/p-Cu2O core-shell (C-S) nanowire (NW) photodiode was fabricated using Cu2O grown by atomic layer deposition (ALD) on a well-ordered Si NW array. Ordered Si nanowires arrays were fabricated by nano-sphere lithography to pattern metal catalysts for the metal-assisted etching of silicon, resulting in a Si NW arrays with a good arrangement, smooth surface and small diameter distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Cu2O/n-TiO2 NW Sputtering on NW~ 1 order in dark[15] p-Cu2O/n-ZnO NW Sputtering on NW~ 1 order in dark…”
mentioning
confidence: 99%
“…42 It was also recently shown that the unique optical and electric properties of TiO 2 unveil the possibility for its use also as photo-catalytic anticorrosion protection of steels. [43][44][45][46][47][48][49] Considering the investigation of T. Tsai and co-authors 50 it is expected that deposited on steel, TiO 2 layers will create photocathode protection under the influence of UV irradiation. This protection property is based on the transfer of photo-generated electrons to the metal substrate, as a result of which its electrode potential becomes more electronegative than its corrosion potential.…”
Section: Introductionmentioning
confidence: 99%